If ‘g’ is the inverse of ‘f’ and f'(x)=11+x3, then g'(x)=

# If $\text{'}g\text{'}$ is the inverse of $\text{'}f\text{'}$ and $f\text{'}\left(x\right)=\frac{1}{1+{x}^{3}}$, then $g\text{'}\left(x\right)=$

1. A

$1+{\left[g\left(x\right)\right]}^{3}$

2. B

$\frac{1}{1+{\left[g\left(x\right)\right]}^{3}}$

3. C

${\left[g\left(x\right)\right]}^{3}$

4. D

$\frac{1}{{\left[g\left(x\right)\right]}^{3}}$

Fill Out the Form for Expert Academic Guidance!l

+91

Live ClassesBooksTest SeriesSelf Learning

Verify OTP Code (required)

### Solution:

We have $g=$ inverse of $f={f}^{-1}$

$⇒g\left(x\right)={f}^{-1}\left(x\right)⇒f\left(g\left(x\right)\right)=x$

Differentiate with respect to $\text{'}x\text{'}$

$f\text{'}\left[g\left(x\right)\right]×g\text{'}\left(x\right)=1$

$\therefore g\text{'}\left(x\right)=\frac{1}{f\text{'}\left(g\left(x\right)\right)}=1+{\left[g\left(x\right)\right]}^{3}$

$\left(\because f\text{'}\left(x\right)=\frac{1}{1+{x}^{3}},\text{\hspace{0.17em}}f\text{'}\left(g\left(x\right)\right)=\frac{1}{1+{\left(g\left(x\right)\right)}^{3}}\right)$

+91

Live ClassesBooksTest SeriesSelf Learning

Verify OTP Code (required)